Giant pure ovarian dysgerminoma in a young 19-year-old patient - Pelaes-Cruz, Elkin J. (2024)
Ovarian dysgerminoma is a very rare neoplasm. It occurs mostly in young womenwith nonspecific clinical manifestations, although they may express abdominalpain, sensation of mass and menstrual alterations. We report the case of a youngmultiparous 19-year-old female patient with sensation of intra-abdominal mass,of progressive growth and associated with oppressive pain. On tomographicexamination an ovarian-dependent adnexal mass was found, so she underwent aright adnexectomy and freezing biopsy plus staging. Macroscopic evaluation revealeda tumor measuring 25 x 20 x 13 cm, weighing 5,760 grams. By microscopic evaluationand immunohistochemistry studies it was diagnosed as pure dysgerminoma. Basedon the average size and history, it was classified as a giant dysgerminoma.